The Effect of Sembukan Leaf Extract (Paederia Foetida) on the Growth of Klebsiella Pneumoniae Bacteria with the Disc Method and the Contact Method - setiyo rini, chylen; Pratiwi, Nova Linda (Universitas Nahdlatul Ulama Surabaya, 2022)
Sembukan leaf (Paederia foetida) is a wild plant which is known to have many benefits and can be used as a medicinal plant. These plants contain bioactive compounds that function as antibacterial. This study aims to determine the ability of sembukan leaf extract to inhibit the growth of Klebsiella pneumoniae. The methods used in this study were disc diffusion and contact methods, with variations in the concentration of curd leaf extract 0%, 25%, 50%, 75% and 100%. The research data obtained were analyzed by One Way ANOVA with 95% confidence level (p<0.05). The best concentration with the disc diffusion method at a concentration of 75% with an inhibitory diameter of 15.25 mm with a strong category and the best percentage of inhibition method on sembukan leaf extract at 69.42% with a bacteristatic category at a concentration of 75%, while the results of the One Way ANOVA test that has been done obtained a significant value of p=0.000 (p<0.05) indicates a significant effect on the administration of sembukan leaf extract against Klebsiella pneumoniae bacteria. The results showed that sembukan leaf extract was able to inhibit the growth of Klebsiella pneumoniae.